Psychophysiology of facial emotion recognition in psychopathy dimensions and oxytocin’s role: A scoping review - Sara Ferreira-Nascimento; Filipa Freire; Diana Prata (PLoS ONE, 2025)
Psychopathy is characterized by social impairments that hinder effective societal functioning. It comprises two main dimensions: “Interpersonal-affective” and “Lifestyle-antisocial,” each associated with distinct patterns of traits and central and peripheral neurocorrelates, particularly concerning social salience and oxytocin function. In this review, we systematically identified and synthesized evidence from studies investigating oxytocin’s role in the psychophysiological correlates of emotion recognition across psychopathy dimensions. However, as no such direct studies were identified, we instead compiled and analyzed research examining these variables separately. A scoping review was conducted to capture studies reporting on psychopathy or oxytocin in relation to facial emotion recognition, whether or not they included central or peripheral psychophysiological measurements – retrieving 66 articles. We found distinct emotion recognition outcomes between psychopathy dimensions, some even with opposing neural activity in response to emotional expressions, particularly those of negative valence, as assessed through neuroimaging, electrophysiology, eye-gazing, and pupillometry. Oxytocin presented suggestive positive/compensatory effects on social salience, enhancing emotion recognition, and increasing pupil dilation, and eye-gazing towards faces, and decreasing brain activation towards negative emotions. This review highlights the critical need for future studies to bridge the gap between psychopathy and oxytocin research by exploring their interaction on shared psychophysiological correlates. Such efforts could facilitate the identification of dimension-specific diagnostic biomarkers and targeted interventions for psychopathy.